Assessing Collector Bias: A Geometric Morphometric Analysis of a Collection of Isolated Clovis Points from the Midcontinent. Issue 2 (4th May 2018) - Ragan, Kathryn; Buchanan, Briggs
ABSTRACT: Clovis points are found across the contiguous United States as isolated surface finds and as elements of assemblages in surface and subsurface deposits. Despite being scattered over the continent, Clovis points exhibit a remarkable degree of standardization, yet there is still a demonstrable level of variation in their shapes across regions. Including isolated points in regional comparative analyses would significantly increase sample sizes and spatial coverage of these analyses; however, the effects of collector bias—the tendency to collect the most typical and aesthetically pleasing points—are unknown. Here, we examine the shape of a sample of isolated Clovis points from the midcontinent using geometric morphometric techniques. We show that resharpening had little effect on the shape of points and that our sample of isolated points are similar in shape to points from assemblages in the midcontinent. Our findings suggest that isolated points have research potential when collector bias is limited.